19F-Labeled NMR Probes for the Detection and Discrimination of Nitrogen-Containing Analytes - Gu, Guangxing; Wang, Chenyang; Zhao, Yanchuan (Synthesis, 2024)
The development of 19F-labeled NMR probes has become a pivotal tool in analytical chemistry. Recent advancements in probe design enable precise identification of nitrogen-containing analytes, significantly enhancing the analysis of these biologically important analytes in complex mixtures. This short review highlights recent progress with probes based on covalent derivatization and dynamic exchange strategies, which yield distinct 19F NMR signals for each nitrogen-containing analyte. These strategies facilitate separation-free multicomponent analysis and chiral discrimination. Discussions will cover design principles, scope, limitations, and strategies to enhance the sensitivity and resolving ability. By addressing current challenges, 19F-labeled NMR probes hold the potential to revolutionize the detection of biologically relevant molecules, catalyzing new discoveries in chemical and biochemical research.1 Introduction2 19F-Labeled Probes Based on Covalent Derivatization2.1 Non-Chiral 19F-Labeled Probes Based on Covalent Derivatization2.2 Chiral 19F-Labeled Probes Based on Covalent Derivatization3 19F-Labeled Probes Based on Dynamic Ligand Exchange3.1 Non-Chiral 19F-Labeled Probes Based on Dynamic Ligand Exchange3.2 Chiral 19F-Labeled Probes Based on Dynamic Ligand Exchange4 Conclusion and Outlook
Keywords: 19F NMR; derivatization reagents; metal complex; molecular recognition; chirality sensing; asymmetric synthesis